2022
DOI: 10.1038/s41467-022-34117-8
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties and ultrafast carrier dynamics of copper iodide thin films

Abstract: As a promising high mobility p-type wide bandgap semiconductor, copper iodide has received increasing attention in recent years. However, the defect physics/evolution are still controversial, and particularly the ultrafast carrier and exciton dynamics in copper iodide has rarely been investigated. Here, we study these fundamental properties for copper iodide thin films by a synergistic approach employing a combination of analytical techniques. Steady-state photoluminescence spectra reveal that the emission at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…[17a, 21] Typically, the radiative recombination rate is in the order of 10 À 11 to 10 À 9 cm 3 s À 1 in GaAs and hybrid perovskites. [21,22] However, the second-order recombination rate for n = 2 samples shows great variation (k 2 � 0), while the values of k 2 for the others are comparable to that for similar hybrid perovskites in the literature. [17b, 19b] In the presence of Rashba splitting, the magnitude of splitting is different in the valence and conduction bands, and an indirect transition is induced.…”
Section: Forschungsartikelmentioning
confidence: 57%
“…[17a, 21] Typically, the radiative recombination rate is in the order of 10 À 11 to 10 À 9 cm 3 s À 1 in GaAs and hybrid perovskites. [21,22] However, the second-order recombination rate for n = 2 samples shows great variation (k 2 � 0), while the values of k 2 for the others are comparable to that for similar hybrid perovskites in the literature. [17b, 19b] In the presence of Rashba splitting, the magnitude of splitting is different in the valence and conduction bands, and an indirect transition is induced.…”
Section: Forschungsartikelmentioning
confidence: 57%
“…To further emphasize our results, we have calculated the T c (Figure A–C) for CsPbCl 3 NCs for all temperatures under consideration. In order to calculate T c , the high-energy tail of the normalized TA bleach is fitted using the Maxwell–Boltzmann (MB) approximation. The detailed explanation of the procedure followed and plots of MB fitting are provided in the Supporting Information (Figure S10). However, after being stimulated by an ultrashort pulse, both holes and electrons populate the higher energy levels rapidly and thermalize within sub picoseconds. ,, They eventually relax to the band edge via carrier–carrier scattering, carrier–phonon scattering, and phonon–phonon scattering .…”
Section: Resultsmentioning
confidence: 99%
“…64 Similar behavior in perovskites has been observed by employing OPTP spectroscopy, and these investigations observed a faster response component (Auger recombination) with increased pump fluences. 49,64,65 Thus, it is fair to ascertain that both absence of Auger recombination process as well as higher penetration depth upon lower pump excitation govern the slower decay of mobility and photoconductivity upon near band gap excitation (Figure 5F).…”
Section: N Qmentioning
confidence: 99%
“…In a material where the Coulombic interaction between the hole and electron pair is strong, such as in the case of CuI, photoexcitation could give rise to bound excitons (CuI exciton binding energy is ≈62 meV) . Li et al observed an ultrafast negative transient absorption signal at 3.7 eV (0.65 eV higher energy than the bandgap bleach signal), which they assigned to free excitons, confirming the existence of strongly bounded excitons. Excitons are quasi-particles formed by bound hole–electron pairs, which in the case of CuI excited at 550 nm, would appear when promoting an electron from the VB to a trap state.…”
mentioning
confidence: 99%